Osteology and relationships of Revueltosaurus callenderi (Archosauria: Suchia) from the Upper Triassic (Norian) Chinle Formation of Petrified Forest National Park, Arizona, United States. Issue 10 (29th September 2021) - Parker, William G.; Nesbitt, Sterling J.; Irmis, Randall B.; Martz, Jeffrey W.; Marsh, Adam D.; Brown, Matthew A.; Stocker, Michelle R.; Werning, Sarah
Abstract: Once known solely from dental material and thought to represent an early ornithischian dinosaur, the early‐diverging pseudosuchian Revueltosaurus callenderi is described from a minimum of 12 skeletons from a monodominant bonebed in the upper part of the Chinle Formation of Arizona. This material includes nearly the entire skeleton and possesses a combination of plesiomorphic and derived character states that help clarify ingroup relationships within Pseudosuchia. A phylogenetic analysis recovers R. callenderi in a clade with Aetosauria and Acaenasuchus geoffreyi that is named Aetosauriformes. Key autapomorphies of R. callenderi include a skull that is longer than the femur, a complete carapace of dermal armor including paramedian and lateral rows, as well as ventral osteoderms, and a tail end sheathed in bone. Histology of the femur and associated osteoderms demonstrate that R. callenderi was slow growing and that the individuals from the bonebed were not young juveniles but had not ceased growing. A review of other material assigned to Revueltosaurus concludes that the genus cannot be adequately diagnosed based on the type materials of the three assigned species and that only R. callenderi can be confidently referred to Revueltosaurus .